2013
DOI: 10.1039/c3ra42497a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis of a TiO2 hollow microsphere assembly from hollow nanoparticles with enhanced photocatalytic activity

Abstract: A novel hierarchical anatase TiO 2 hollow microsphere (TiO 2 -HMS) assembly synthesised from TiO 2 hollow nanoparticles (TiO 2 -HNP), denoted TiO 2 -HMS-HNP, was rapidly fabricated by a simple hydrothermal route in a Ti(SO 4 ) 2 -NH 4 F-H 2 O 2 mixed solution at 180 uC for only 3 h. The influence of NH 4 F and H 2 O 2 on the formation of TiO 2 -HMS-HNP was studied. A novel mechanism for the formation of TiO 2 -HMS-HNP based on a H 2 O 2 -assisted fluoride-induced self-transformation (FIST) process is proposed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The surface-fluorinated TiO2-HMS precursor was prepared in the presence of fluoride ions according to our previously reported method [44]. First, 7.5 mmol of Ti(SO4)2 and 7.5 mmol of NH4F were dissolved in 65 mL of water under magnetic stirring.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface-fluorinated TiO2-HMS precursor was prepared in the presence of fluoride ions according to our previously reported method [44]. First, 7.5 mmol of Ti(SO4)2 and 7.5 mmol of NH4F were dissolved in 65 mL of water under magnetic stirring.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In this study, TiO2-HMSs were prepared by hydrothermal treatment of a mixed Ti(SO4)2-NH4F-H2O2 solution according to our previously reported method [44]. Considering that surface-fluorinated TiO2-HMSs should possess high thermal stability, the effect of the calcination temperature on the structure and photocatalytic activity of the as-prepared TiO2-HMSs was investigated, where the photocatalytic activity was evaluated by photocatalytic oxidation of acetone under ultraviolet (UV) irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 , SiO 2 , ZnO, Fe 3 O 4 , SnO 2 , CeO 2 ) have attracted much attention since the past decades for their special properties in photocatalysis, sensors, Li‐ion batteries, or drug delivery . This morphology provides a high surface area, low density, effective light harvesting, and particular optical, electrical, mechanical, photo‐electrochemical, and catalytic properties among others . Moreover, the void space confers high cargo loading/releasing capacity interesting for drug, peptides or other biological molecule delivery systems .…”
Section: Introductionmentioning
confidence: 99%
“…This morphology provides a high surface area, low density, effective light harvesting, and particular optical, electrical, mechanical, photo‐electrochemical, and catalytic properties among others . Moreover, the void space confers high cargo loading/releasing capacity interesting for drug, peptides or other biological molecule delivery systems . Three different routes of synthesis are known for obtaining hollow structures materials.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 3D TiO2 spheres have been synthesized through various methodologies, including solvothermal and hydrothermal reaction (Liao et al, 2011;Sun et al, 2011;Gao and Sun, 2014), electrochemical process (Tang et al, 2012) and template assisted calcination method (Bai et al, 2012). Cai et al (2013) reported the fabrication of hierarchical TiO2 hollow microspheres by a rapid hydrothermal reaction. It was reported that these TiO2 microspheres were constructed by TiO2 hollow nanoparticles and the as-synthesized…”
Section: D Tio2 Spheresmentioning
confidence: 99%